2022
DOI: 10.3390/foods11152180
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Berry Pomace on Quality Changes of Beef Patties during Refrigerated Storage

Abstract: This study aims to evaluate the ability of raspberry and blackberry pomace to inhibit lipid oxidation and prolong the refrigerated storage of beef patties. Berry pomace was incorporated into beef patties at the concentration of 1, 3, and 5%. Packed patties were stored for 9 days at 4 °C temperature and the quality of the meat was evaluated on the 0, 3rd, 6th, and 9th day. The natural mass loss during storage, the pH as well as the lipid oxidation were evaluated by thiobarbituric acid-reactive substance (TBARS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Raspberries ( Rubus ideaus L.), a red fruit abundant in bioactive compounds, such as phenolics, organic acids, vitamins, minerals, and anthocyanins with potent antioxidant properties [ 8 ], can potentially enhance the oxidative stability of omega-3-enriched meat products. Previous studies have demonstrated that raspberry extracts can enhance the oxidative stability of fish oil (rich in n-3 PUFAs) [ 9 ] and various meat products, such as pastirma [ 10 ], meatballs [ 11 ], and burgers [ 12 ]. The mechanism by which raspberry extracts exert their antioxidant effects can be attributed to the presence of anthocyanins.…”
Section: Introductionmentioning
confidence: 99%
“…Raspberries ( Rubus ideaus L.), a red fruit abundant in bioactive compounds, such as phenolics, organic acids, vitamins, minerals, and anthocyanins with potent antioxidant properties [ 8 ], can potentially enhance the oxidative stability of omega-3-enriched meat products. Previous studies have demonstrated that raspberry extracts can enhance the oxidative stability of fish oil (rich in n-3 PUFAs) [ 9 ] and various meat products, such as pastirma [ 10 ], meatballs [ 11 ], and burgers [ 12 ]. The mechanism by which raspberry extracts exert their antioxidant effects can be attributed to the presence of anthocyanins.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that freeze-dried apple pomace (AP) and freeze-dried blackcurrant pomace (BC) possess high antimicrobial [ 32 , 36 , 37 , 46 ] and antifungal [ 40 , 47 ] activity against a broad spectrum of pathogenic bacteria strains and fungi. It is also known that by-products from the berry/fruit industry can improve the sensory properties (i.e., colour, flavour, moisture, and texture) of different types of foods [ 36 , 46 , 48 , 49 , 50 , 51 ]. The influence of juices, extracts and vinegar has also been reported on the quality and sensory parameters of pork [ 52 , 53 , 54 ], poultry [ 53 , 54 , 55 , 56 ], beef [ 57 , 58 , 59 , 60 ], and LM [ 61 , 62 ]; however, information about marinades prepared using AW–LAB–berry/fruit combinations is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Waste generated after the processing of fruits is a promising source of valuable bioactive compounds. In recent years, researchers have established that pomace is a valuable source of nutrients such as phenolic compounds, pigments, dietary fibers, essential oils, enzymes, vitamins, and fatty acids [2,24,25], and pomace is no longer seen as a waste and can be used as potential dietary additive and natural colorant, nutritional value food supplement or functional ingredient in different food matrices [26,27]. The physicochemical properties of blackberry pomace play a pivotal role in influencing the texture and stability of food products [28].…”
Section: Introductionmentioning
confidence: 99%